Dry-whip phenomenon in on-board rotordynamics: Modeling and experimentation. (24th November 2021) - Briend, Yvon; Chatelet, Eric; Dufour, Régis; Andrianoely, Marie-Ange; Legrand, Franck; Sousa, Marcelo Samora; Steffen, Valder; Baudin, Sophie
Abstract: This paper addresses rotor–stator contact issues, especially the dry-whip phenomenon, as caused by base excitations. So far, this particular instability in the case of direct rub between shaft and stator was only shown by experiments to occur in response to mass unbalance excitation during run-up or run-down and/or to external disturbance such as direct impact applied to the rotor. The present paper aims to demonstrate that it can also be triggered by external forces coming from the rigid base motion. To this end, both numerical and experimental approaches are employed. A rotor finite element model combining on-board motions with shaft-stator rub impact is first proposed. This model is validated with a rotor test-rig supported by hydrodynamic bearings and mounted on a multi-axial hydraulic shaker and subject to a harmonic base motion. The dry-whip is then shown experimentally by using a base shock excitation consisting of two transverse translations, which is later confirmed numerically. The influence of important parameters on the dynamic behavior of the system is also assessed, such as the hydrodynamic bearing nonlinearities, the amplitude and direction of the base translations and the dry friction coefficient. Highlights: FEM of on-board rotor on journal bearings with rotor–stator contacts. Experimental validation of the model. Evidencing of the dry-whip phenomenon due to shock base translations. Influence of the base motion amplitude and direction on the dry-whip occurrence. Video of the dry-whip occurrence performed by a high-frequency camera.